PERLINDUNGAN HAK ULAYAT MASYARAKAT HUKUM ADAT DALAM KEGIATAN PERTAMBANGAN - Rumihin, Ony Frengky; Marleno, Risma (Jurnal HUKUM BISNIS, 2026)
This study examines the position of customary rights in the context of mining permit conflicts in Indonesia. Although customary rights have been recognized in various regulations, including the 1945 Constitution and the Basic Agrarian Law (UUPA), in practice, these rights are often ignored in the mining permit granting process. Conflicts arise when mining permits are issued for land that falls within the customary rights area of indigenous peoples, without involving them in the decision-making process. The purpose of this study is to determine the position of customary rights in relation to mining permits and the challenges faced by indigenous peoples in defending their rights. The results of this study show that although the customary rights of indigenous peoples are recognized in various regulations, this recognition is often not consistently applied in the practice of mining licensing. Indigenous peoples are often not involved in the licensing process, and their customary rights are often ignored when permits are granted for the exploitation of natural resources in their territories. This has led to conflicts between indigenous peoples and mining companies and the government. Keywords: Land, Customary Rights, Indigenous Peoples, Mining.